IMPLEMENTASI PEMBELAJARAN MAKHORIJUL HURUF BERBASIS ALAT PERAGA MODEL GIGI EDUKASI DALAM PEMBELAJARAN AL-QUR’AN DI MI AL-IKHLAS - Firda Zakiyatur Rofi'ah; Nabila Mahfudhotin Ismaillia; Septya Relan Alivia Nanda Baisroh; Putri Lestari; Linda Ayu Sahara; Rafi Ajrul Baha' Udin; Ulfa Nur Fitri Aprilia (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the implementation of makhorijul huruf learning based on an educational dental model teaching aid in Al-Qur’an learning at MI Al-Ikhlas, to identify students’ responses to its use, and to determine the supporting and inhibiting factors in its implementation. This research employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the use of the educational dental model teaching aid helped students understand makhorijul huruf more concretely through the visualization of the positions of the tongue, teeth, lips, oral cavity, and throat when pronouncing hijaiyah letters. This media improved students’ understanding of the articulation points of letters, facilitated their ability to distinguish letters with similar sounds, and increased their motivation, attention, and active participation during the learning process. The implementation of the educational dental model teaching aid also made learning more engaging and effective compared to conventional methods that rely solely on lectures and verbal imitation. Supporting factors included students’ tendency to understand material more easily through visual learning, teacher support, and the use of concrete and interactive learning media.